2014
DOI: 10.1371/journal.pone.0085002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 131I-Anti-Angiotensin II Type 1 Receptor Monoclonal Antibody as a Reporter for Hepatocellular Carcinoma

Abstract: BackgroundFinding a specific agent is useful for early detection of tumor. Angiotensin II type 1 receptor (AT1R) was reported to be elevated in a variety of tumors and participate in tumor progression. The aim of our study was to evaluate whether 131I-anti-AT1R monoclonal antibody (mAb) is an efficient imaging reporter for the detection of hepatocellular carcinoma.Methodology/Principal FindingsAT1R mAb or isotype IgG was radioiodinated with 131I and the radiochemical purity and stability of the two imaging age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our results indicated that Ang-(1-7) arrested the proliferation of tumor cells by downregulating AT 1 R and upregulating AT 2 R and MasR. Overexpression of AT 1 R has been demonstrated in a variety of tumors in vitro and in vivo, such as hepatocellular carcinoma and breast and ovarian cancer (7,20,21). AT 1 R induces tumor cell proliferation by two main intracellular mechanisms: AT 1 R activates phosphatidylinositol, utilizes two main second messengers, triphosphoinositol and diacylglycerol and causes an increase in cytosolic Ca 2+ content, a process linked to mitogenesis in several cell types (22); and AT 1 R modulates the activity of protein tyrosine kinases, which are coupled to the receptors of several growth factors and are involved in the transduction of growthinducing signals.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our results indicated that Ang-(1-7) arrested the proliferation of tumor cells by downregulating AT 1 R and upregulating AT 2 R and MasR. Overexpression of AT 1 R has been demonstrated in a variety of tumors in vitro and in vivo, such as hepatocellular carcinoma and breast and ovarian cancer (7,20,21). AT 1 R induces tumor cell proliferation by two main intracellular mechanisms: AT 1 R activates phosphatidylinositol, utilizes two main second messengers, triphosphoinositol and diacylglycerol and causes an increase in cytosolic Ca 2+ content, a process linked to mitogenesis in several cell types (22); and AT 1 R modulates the activity of protein tyrosine kinases, which are coupled to the receptors of several growth factors and are involved in the transduction of growthinducing signals.…”
Section: Discussionmentioning
confidence: 59%
“…Although the literature supports a beneficial role for Ang-(1-7) in lung cancer and prostate cancer (5,6), the effects of Ang-(1-7) on other tumors have not been evaluated. We recently confirmed that AT 1 R was overexpressed in hepatocellular carcinoma tissue using a murine H22 hepatoma model (7). Which receptor of Ang-(1-7) is activated to mediate its effects is much speculated.…”
Section: Introductionmentioning
confidence: 81%
“…The relationship between the use of AT1R blockers and cancer risk has drawn significant attention since 2010 [ 18 ]. Accumulating evidence has shown that AT1R blockers are associated with decreased risks of colorectal cancer, lung cancer, and prostate cancer [ 19 , 20 ]. However, some studies have also found that there is no significant association between the use of AT1R blockers and other human cancers, such as liver, gastric, and hematological malignancies [ 16 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCC-targeted antibodies labeled with 131 I have been intensively studied for the treatment of HCC, with the most common antibodies including mouse anti-human monoclonal antibody fragment HAb18F(ab) 2 (metuximab), ChTNT human-mouse chimeric antibody, hepama-1 HCC cell membrane monoclonal antibody, CD133 monoclonal antibody, anti-hepatitis B virus antibodies, anti-machine protein monoclonal antibody, and anti-human HCC transferrin monoclonal antibody. Radioimmunotherapy agents used for HCC with clinical trials include 131 I-metuximab, 131 I-chTNT, and 131 I-hepama-1 monoclonal antibody [76,77].…”
Section: Radioimmunotherapymentioning
confidence: 99%
“…131 I acts to treat the surrounding tumor cells, causing new necrosis, while the chTNT monoclonal antibody expands to the newly necrotic area to continuously expand it to achieve the therapeutic goal. At present, 131 I-chTNT is considered to have a therapeutic effect on lung cancer, brain cancer, and liver cancer, among others [76,80].…”
Section: I-chtntmentioning
confidence: 99%